2022
DOI: 10.3389/fmars.2022.1002502
|View full text |Cite
|
Sign up to set email alerts
|

Widespread occurrence of endogenous cellulase production and glycosyl hydrolase in grapsoid crabs along the land-sea transition indicates high potential for mineralisation of mangrove production

Abstract: Previous studies on mangrove carbon utilisation and mineralisation were focused on mangrove sesarmid crabs (Grapsoidea: Sesarmidae) because they are initial processors of mangrove organic carbon. Grapsoid crabs from other families and habitats were generally ignored although they also perform various levels of herbivory. It remains unclear how the herbivorous crabs utilise the production from mangrove or vascular plants because of the high C/N ratio and high structural carbon content of these materials. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…The detritivores enriched genes mainly related to hemicellulose and pectin degradation. The variations in CAZyme composition are also higher among the detritivorous species that partially reflect their diverse microhabitat preference (e.g., more muddy sediment that contains more organic matter versus sandy substratum that contains more animal meiofauna), and hence variations in organic matter content in diet, which is consistent with previous reports on higher cellulase activities in crab species having a greater plant biomass in diet [20,76]. This provides further support to our hypothesis that endosymbiotic cellulolytic microbes play an important role in lignocellulose degradation in most crab species but their abundance is strongly correlated with dietary preference, and thus enhancing their capacity for digestion of mangrove leaves and plant detritus.…”
Section: Enrichment Of Microbial Cellulolytic Capacity In Mangrove He...supporting
confidence: 90%
See 1 more Smart Citation
“…The detritivores enriched genes mainly related to hemicellulose and pectin degradation. The variations in CAZyme composition are also higher among the detritivorous species that partially reflect their diverse microhabitat preference (e.g., more muddy sediment that contains more organic matter versus sandy substratum that contains more animal meiofauna), and hence variations in organic matter content in diet, which is consistent with previous reports on higher cellulase activities in crab species having a greater plant biomass in diet [20,76]. This provides further support to our hypothesis that endosymbiotic cellulolytic microbes play an important role in lignocellulose degradation in most crab species but their abundance is strongly correlated with dietary preference, and thus enhancing their capacity for digestion of mangrove leaves and plant detritus.…”
Section: Enrichment Of Microbial Cellulolytic Capacity In Mangrove He...supporting
confidence: 90%
“…Crustaceans can encode endogenous Carbohydrates Active enZymes (CAZymes) for lignocellulose degradation, which are hypothesized to be responsible for the degradation of algal cell wall, a major component in their omnivorous diet [15,16]. Transcriptomic and enzyme assay studies have confirmed the production of endogenous cellulolytic enzymes in herbivorous decapod species [17][18][19], including sesarmid crabs [20,21]. However, it remains largely unclear that if mangrove herbivorous crabs possess complete metabolic pathways to degrade lignocellulose, or if they require a symbiotic microbiome to complement the digestion process as the situation observed in terrestrial isopods [22] and termites [23][24][25][26], due to limited clues.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, members of Mycoplasmataceae and Vibrio are also known to possess cellulolytic genes (Fraune & Zimmer, 2008;Gao et al, 2010;Rasmussen et al, 2021). The host endogenous genomic toolkit in the mangrove herbivorous crabs (Lee & Lee, 2022;Miyake & Baba, 2022) together with the core cellulolytic microbiome appear to form a dual-lignocellulolytic system to achieve efficient digestion of plant materials and hence maximize the nutritional gain for both (Hu et al, 2013;Hui et al, 2024;Salem et al, 2020).…”
Section: Functional Association and Codiversification Of Mangrove Cra...mentioning
confidence: 99%
“…Hu et al, 2018;Newsome et al, 2020). Endogenous cellulolytic enzymes were found in mangrove crab transcriptome (Lee & Lee, 2022), but the study on the role of microbes is limited. Tongununui et al (2021) characterized the gut microbe composition of three mangrove-associated sesarmid species using 16S sequencing, and they detected cellulase and nitrogenase activities in the intestine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation